Evaluasi Pelaksanaan Proses Pembelajaran pada Dosen Muda Peserta Pelatihan Pekerti Universitas Negeri Manado - Jefry H. Tamboto (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study is evaluation research aimed at assessing the effectiveness of the teaching process implemented by young lecturers who have attended the Basic Instructional Skills Improvement Training (Pekerti) at Universitas Negeri Manado. A sample of 20 lecturers was selected using simple random sampling techniques. The results show that (1) The preparation of the teaching plan by the lecturers at Unima was well done, with 90% of lecturers demonstrating good to excellent performance in preparing their teaching plans. In comparison, only 10% showed less satisfactory performance. (2) The implementation of the teaching process was also well conducted, with 95% of lecturers carrying out the teaching process according to good to excellent criteria and only 5% falling into the less satisfactory category. Although the overall teaching implementation was adequate, several aspects needed improvement, namely the use of media and teaching tools, providing feedback on learning outcomes, and offering follow-up activities. These three aspects should be a primary focus in future training programs like Pekerti to enhance the quality of teaching. The findings provide important recommendations for the development of training programs and the improvement of teaching quality at higher education institutions, especially in the context of developing young lecturers' competencies.